El animal soberano: "María Estuardo" de Schiller - Villacañas, José Luis (Analysis. Journal of Philosophical Research, 2015)
Resumen: Este trabajo ofrece una reflexión sobre el drama de Schiller María Estuardo desde la perspectiva de las Consideraciones políticas sobre los golpes de Estado de Gabriel Naudé. Palabras clave: Romanticismo, política, soberanía.   Abstract: This paper offers a reflection on Schiller’s drama Mary Stuart from the point of view of Gabriel Naudé’s Political Considerations on Coups d’Êtat. Keywords: Romanticism, Politics, Sovereignty.